2000
DOI: 10.1038/sj.bmt.1702545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastrointestinal inflammation and age on the pharmacokinetics of oral microemulsion cyclosporin A in the first month after bone marrow transplantation

Abstract: Cyclosporin A (CsA) absorption is highly variable in BMT patients. Neoral, a new microemulsion formulation of CsA, permits increased absorption with less variable pharmacokinetic parameters in non-BMT patients. We evaluated the pharmacokinetics of CsA after BMT in patients received microemulsion CsA. Two oral doses of 3mg/kg were given 48 h apart between 14 and 28 days after allogeneic BMT in 20 adults, and one dose in seven children, while subjects were receiving a continuous i.v. infusion of CsA. Whole blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 27 publications
1
44
2
Order By: Relevance
“…12,13,15 However, we conducted part of our study at a later point in the post transplant period, when GI inflammation was improved; the pharmacokinetics of CsA in HSCT recipients may correspond more closely to those for solid organ transplant recipients during the period of time studied in our investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,15 However, we conducted part of our study at a later point in the post transplant period, when GI inflammation was improved; the pharmacokinetics of CsA in HSCT recipients may correspond more closely to those for solid organ transplant recipients during the period of time studied in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,21 Several pediatric solid organ transplant centers are using a three times daily dosing schedule instead of twice daily. 39,40 It has been reported that the three times daily dosing schedule of CsA in children helped to avoid deleterious peak levels with less fluctuation in blood concentration; these results have been obtained without any significant change of the average concentration of CsA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GI inflammation may also affect absorption, with higher levels observed in patients with mucositis or GVHD. 2 The availability of an oral microemulsion formulation (Neoral, Novartis, Sydney, Australia) has improved problems with erratic absorption, 3,4 but high inter-patient variability in absorption and metabolism has resulted in monitoring of CsA levels as standard practice. Given orally twice daily, CsA levels in allo-SCT patients have traditionally been performed 12 h after the preceding dose (C0), although the relationship of trough levels to toxicity and the effectiveness of prevention of GVHD is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a model that predicts ciclosporin pharmacokinetics and dose requirements to achieve the desired therapeutic target in an individual HSCT patient would be highly useful. CsA pharmacokinetic studies in HSCT recipients are scarce and most have evaluated only small numbers of subjects [9, [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%